Alkane Degradation and Detection of Mono-xygenase Gene from Alcanivorax sp. from Jakarta Bay - Thontowi, Ahmad; Yopi, Yopi (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2011)
Alkanes is a major component of crude oil that can be hydrolized by enzyme alkane monooxygenase from bacteria. Nine oil-degrading bacteria were analyzed their capability to degrade alkanes (pristane and paraffin). The result of growth test on paraffin and pristane were showed that 9 isolates could be devided into two groups. First group (BL09, BL31 and BL45) could degrade both paraffin and pristane, and second group (BL01, BL06, BL44, BL057, BL058 and BL071) preferred to degrade paraffin than pristane. Three isolates (BL09, BL31 and BL45) have activity to decrease paraffin and pristane until less 50% remain. Based on homology analysis of 16S rRNA gene sequences showed that isolates No. BL09, BL31 and BL45 were identified as Alcanivorax sp. and the partial sequences of the alkB gene from those three isolates are showing 66-68% of identity compare with some mono-oxygenase gen from database of genbank.Keywords: biodegradation, alkane, monooxygenase, cloning, alkB